A New Iterative Joint Detection and Decoding Algorithm for V-BLAST Architecture - Meng-Ying Tsai; Yousefi, S. (IEEE signal processing letters, 2009)
Soft iterative detection and decoding techniques have been shown to be able to achieve near-capacity performance in multiple-antenna systems. To obtain the optimal soft information by marginalizing over the entire observation space is intractable: one must resort to suboptimal methods to implement such receivers. Although list-type detectors such as those founded upon the sphere decoding algorithm provide outstanding error performance, issues such as the optimal initial sphere radius, optimal radius update strategy, and their highly variable computational complexity are still unresolved. In this paper, a new detection scheme is proposed addressing the above issues. Our simulation results show that by sacrificing less than 2 dB at error rate of 10 -5 , we are able to gain up to 38.6% complexity reduction as well as a detector structure that is more suitable for practical system implementation.